2013
DOI: 10.4236/ajac.2013.46041
|View full text |Cite
|
Sign up to set email alerts
|

Stability Indicating RP-HPLC Method for the Determination of Dronedarone Hydrochloride and Its Potential Process-Related Impurities in Bulk Drug and Pharmaceutical Dosage Form

Abstract: Simple, sensitive and accurate stability indicating analytical method for dronedarone has been developed and validated using RP-HPLC technique. Developed method is used to evaluate the assay and related substances of dronedarone drug substance and tablets (Multaq ® ). The drug substance was subjected to the stress conditions such as hydrolysis (acid and base), oxidation, photolysis and thermal degradation as per International Conference on Harmonization (ICH) prescribed stress conditions to show the stability-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The RRT of degradant in alkaline, neutral and peroxide condition matches with impurity-4 while a second degradant was observed in the chromatogram of peroxide stress sample with RRT of 1.16 matches with imp-6 (Landge et al, 2013).…”
Section: Force Degradation Studiesmentioning
confidence: 72%
See 2 more Smart Citations
“…The RRT of degradant in alkaline, neutral and peroxide condition matches with impurity-4 while a second degradant was observed in the chromatogram of peroxide stress sample with RRT of 1.16 matches with imp-6 (Landge et al, 2013).…”
Section: Force Degradation Studiesmentioning
confidence: 72%
“…The sample recovery in a formulation was in good agreement with their respective label claims and that suggested non-interference of formulation excipients in the estimation. The cited literature (Landge et al, 2013) did not report any degradation in alkaline and neutral conditions and moreover the stress conditions applied were milder, even though the degradation was seen with appearance of resolved peaks. Hence the drug can be analyzed in presence of its degradation product indicates that the proposed method is stability indicating.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The LC method used a linear elution of gradients and a wavelength of detection of 220 nm. Various solvents, temperatures and pH levels were analysed for chromatographic behaviour of the considerable amount of contamination (Landge et al, 2013).…”
Section: Pro Iling Of Impurities By Rp-hplc 1h Nmrmentioning
confidence: 99%
“…It is a new active substance, and there is no official pharmacopoeial procedure available [6]. Literature overviews confess that drug was estimated by different analytical strategies such as spectrophotometric [7], highperformance liquid chromatography [8][9][10][11][12][13][14][15][16][17], and liquid chromatography mass spectrometry [18,19] in bulk drugs and formulation of dronedarone. From the review, it was found that there were no reported methods for the estimation of elemental impurity, i.e., nickel in dronedarone.…”
Section: Preparation Of Nickel Standard Stock Solution (Solution A)mentioning
confidence: 99%